2021
DOI: 10.1002/cti2.1319
|View full text |Cite
|
Sign up to set email alerts
|

Decline in neutralising antibody responses, but sustained T‐cell immunity, in COVID‐19 patients at 7 months post‐infection

Abstract: Objectives This study aimed to explore the severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2)‐specific humoral responses and T‐cell responses in patients who have recovered from coronavirus disease 2019 (COVID‐19) to understand the natural protective immune responses and to facilitate the development of vaccines. Methods We conducted a combined assessment of the changes in neutralising antibody levels and SARS‐CoV‐2‐specific T‐cell responses over time in 27 patients up to 7 months after infection. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 42 publications
1
28
0
Order By: Relevance
“…On the other hand, the durability of immunity to SARS-CoV-2 remains unclear since there is a decline in circulating antibody titres a few months after recovery or vaccination [148][149][150]. In turn, some authors have found sustained T-cell immunity despite a decline in the antibody response months after infection [151,152], suggesting that other immune components contribute to protective immunity.…”
Section: Immune Correlates Of Protection From Sars-cov-2 Infectionmentioning
confidence: 99%
“…On the other hand, the durability of immunity to SARS-CoV-2 remains unclear since there is a decline in circulating antibody titres a few months after recovery or vaccination [148][149][150]. In turn, some authors have found sustained T-cell immunity despite a decline in the antibody response months after infection [151,152], suggesting that other immune components contribute to protective immunity.…”
Section: Immune Correlates Of Protection From Sars-cov-2 Infectionmentioning
confidence: 99%
“…Long et al found 93% of asymptomatic individuals to have a reduction in anti-SARS-CoV-2 antibody levels during the early convalescent phase (5). Chen et al found a significant decline in anti-S-RBD antibodies 7 months after the infection in hospitalized cases (25). The decline in antibody levels to N and S-RBD after 5 months was also reported by Gaebler et al (26).…”
Section: Discussionmentioning
confidence: 59%
“…These findings along with recent studies from COVID-19-recovered individuals show persistent multi-functional SARS-CoV-2 antigen–specific memory, suggest that these cells could contribute to rapid recall responses [ 16 ]. Few other studies also reported that convalescent-phase SARS-CoV-2-specific T cells generate broader and persistent immune responses even when neutralizing antibodies declined [ 1 , 17 , 44 ] and these T cell reposes were maintained at least 10 months after infection [ 3 , 17 ]. In addition to this, our findings also suggest that there was a good immune correlation observed between the immune parameters and SARS-CoV-2-specific antibodies.…”
Section: Discussionmentioning
confidence: 99%